Using coupled micropillar compression and micro-Laue diffraction to investigate deformation mechanisms in a complex metallic alloy Al13Co4 - Bhowmik,A; Dolbnya,I; Britton,TB; Jones,NG; Sernicola,G; Walter,C; Gille,P; Dye,D; Clegg,WJ; Giuliani,F (Applied Physics Letters, 2016)
In this study, we have used in-situ micro-Laue diffraction combined with micropillar compression of focused ion beam milled Al13Co4 complex metallic alloy to investigate the evolution of deformation in Al13Co4. Streaking of the Laue spots shows that the onset of plastic flow occurs at stresses as low as 0.8 GPa, although macroscopic yield only becomes apparent at 2 GPa. The measured misorientations, obtained from peak splitting, enable the geometrically necessary dislocation density to be estimated as 1.1 1013 m-2.